PENGARUH FINANCIAL DISTRESS, UMUR PERUSAHAAN, AUDIT TENURE, KOMPETENSI DEWAN KOMISARIS PADA KECEPATAN PUBLIKASI LAPORAN KEUANGAN - Krisnanda, I Gede Wahyu; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2017)
This study aims to determine how the effect of financial distress, the age of the company, audit tenure and competence of the commissioners on the velocity of publication of the annual financial statements of financial sector services company registered insurance sub-sector in BEI period 2013-2015. Samples obtained a total of 11 companies with 33 observations. Data analysis used the multiple linear regression. Results from the study showed that the financial distress and audit tenure no significant effect on the velocity of publication of the annual financial statements. Age companies have negative effect on the velocity of publication of the annual financial statements. Competence commissioners positive effect on the velocity of publication of financial statements. Advice can be given to the company to pay more attention in preparing the annual financial statements for the right time with the selection of a competent company attributes.
Keywords: financial distress, the age of the company, the audit tenure, the competence of the board of commissioners, the velocity of publication of the annual financial statements